An evolutionary perspective on managing the ephemeral architecture of organisational creativity. (1st January 2013) - Dobson, Stephen; Breslin, Dermot
Information is widely acknowledged as a primary resource for the 21st century organisation. Strategies for managing information – its acquisition, communication, use, storage, retrieval and architecture – have gained much attention in literature and practice. We argue here that adaptability, primarily through creative innovation, is emerging as an equally critical resource ensuring organisational survival and expansion. However, mapping the processes and human activity systems which form this altogether more ephemeral architecture is a more problematic area of management. Here we principally draw upon evolutionary approaches as a useful means to further enrich the theory of 'soft' systems. In doing so we aim to provide a viewpoint from which to conceptualise the tacit complexity of organisational innovation as a human activity system supporting the transformation and evolution of ideas.